Power spectrum from weak-shear data - Bartelmann, Matthias; Schneider, Peter (Arxiv, 1999)
We demonstrate that the aperture mass as a measure for cosmic shear closely approximates (to better than ~5%) the scaled and shifted power spectrum of the projected mass density. This cosmological weak-lensing information can thus be used to directly infer the projected matter power spectrum with high accuracy. As an application, we show that aperture-mass observations can be used to constrain the cosmic density parameter and the power-spectrum amplitude. We show that, for a particular example, it should be possible to constrain Omega_0 to within ~ +/- 27%, and sigma_8 to within ~ +/- 8% using weak-shear data on a square-shaped field of 8 degrees side length.